Istiṭāʿah Dalam Ibadah Haji: Analisis Terhadap Sistem Penggiliran Haji Malaysia: Istiṭāʿah in Hajj: An Analysis on Malaysian Hajj Queuing System - Man, Sa’adan; Syed Jaafar, Syed Mohd Jeffri; Musa, Lokman (Jurnal Fiqh, 2024)
The issue of Malaysian Hajj pilgrims facing excessively long waiting periods for their turn has been a topic of frequent discussion among various stakeholders. Individuals who registered for Hajj in 2023 are estimated to wait approximately 148 years to perform the pilgrimage. Although the actual waiting period may be shorter than this estimate, it highlights significant weaknesses in the current queuing system. The existing system, introduced by Tabung Haji Malaysia (TH) in 1995, operates on a first-come, first-served basis. This method has been widely criticized for not aligning with the actual prerequisites for Hajj obligations. It includes individuals who do not yet meet the conditions of obligation, such as children and those lacking financial capability, in the queue. Conversely, those who fulfil the conditions of obligation and financial capability are not prioritized and must endure an extended waiting period. This paper aims to analyse this issue and propose several recommendations to improve the queuing system. The study employs qualitative methods and field data, which are analysed using critical, deductive, and inductive analysis techniques. The findings indicate that the current Hajj queuing system used by TH requires a thorough review, as it does not meet at least two essential Hajj conditions: being of legal age (mukallaf) and possessing financial capability (istiṭāʿah māliyyah), for many of the registrants in the queue. This paper will suggest several improvement methods to enhance the efficiency of the Hajj queuing system and ensure it adheres to the criteria established by Islamic law.